2014
DOI: 10.1130/g35001.1
|View full text |Cite
|
Sign up to set email alerts
|

Seismic evidence for a crustal magma reservoir beneath the upper east rift zone of Kilauea volcano, Hawaii

Abstract: An anomalous body with low Vp (compressional wave velocity), low Vs (shear wave velocity), and high Vp/Vs anomalies is observed at 8-11 km depth beneath the upper east rift zone of Kilauea volcano in Hawaii by simultaneous inversion of seismic velocity structure and earthquake locations. We interpret this body to be a crustal magma reservoir beneath the volcanic pile, similar to those widely recognized beneath mid-ocean ridge volcanoes. Combined seismic velocity and petrophysical models suggest the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 41 publications
4
34
1
Order By: Relevance
“…An anomalous body with low-V p , low-V s , and high-V p ∕V s value is resolved at 8-11 km depth beneath the upper ERZ of Kilauea volcano. Lin et al [2014] recently suggested the presence of 10% melt in a cumulate magma mush in this area based on petrophysical modeling.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…An anomalous body with low-V p , low-V s , and high-V p ∕V s value is resolved at 8-11 km depth beneath the upper ERZ of Kilauea volcano. Lin et al [2014] recently suggested the presence of 10% melt in a cumulate magma mush in this area based on petrophysical modeling.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Perhaps increased magma supply to Mauna Loa volcano causes a drop in supply to Kīlauea (Gonnermann et al, 2012). Once magma enters the Kīlauea plume, it could be diverted away from the shallow reservoir, perhaps as intrusions into the crust or lower shield (Lin et al, 2014). A subhorizontal mantle pathway of magma transport at ~30 km depth, interpreted by Wright and Klein (2006; see also Wolfe et al, 2003), might be a zone within which magma could stall or be diverted.…”
Section: Magma Supply Drops During Periods Of Mainly Explosive Activitymentioning
confidence: 99%
“…In the plutonic record this is often expressed as complex time‐transgressive mineral and magnetic fabrics with evidence for both fluid and granular (crystal‐crystal) interactions [ Collins et al ., ; Gutiérrez et al ., ; Holness et al ., ; Jerram et al ., ; Nicolas , ; Paterson , ; Sawyer , ] and in the volcanic record by the eruption of crystal‐rich magmas with a complex crystal cargo [ Bachmann et al ., ; Charlier et al ., ; Klemetti and Clynne , ; Lindsay et al ., ; Thomson and Maclennan , ] (see Figure ). Persistent crystal‐rich conditions in basaltic magma bodies have also been inferred based on seismic evidence from ocean islands and mid‐ocean ridges [ Lin et al ., ; Sinton and Detrick , ] and by the occurrence of picrites [ Rhodes , ]. Collectively, these observations have been rationalized with the hypotheses that they are a crystal‐rich mush, waxing and waning in response to open‐system input and cooling.…”
Section: Introductionmentioning
confidence: 99%